Cottonseed and Soy-bean agro-industrial by-products used in feedlot cattle diet: effects on beef fatty acid profile and quality parameters - Angelo, Polizel Neto [UNESP]; Oliveira, Roça Roberto de [UNESP]; Branco, Arnandes Renata Helena [UNESP]; Martins, Bonilha Sarah [UNESP]; Araújo, Claudio Vieira de [UNESP]; Barros, Gomes Helen Fernanda [UNESP]; Cecconelo, Bento Felipe [UNESP] (FapUNIFESP (SciELO), 2022)
Beef composition are directly influenced by the dietary fat, particularly in ruminants, due to rumen biohydrogenation, which promotes alterations in the dietary fatty acid (FA) profile and affects the meat quality. Beef sensorial, chemical, and FA compositions of intramuscular and subcutaneous fat were evaluated, from 40 Nellore males finished on feedlot diet based, containing cottonseed (CSB) and soybean by-product (SOB) as agro-industrial by-product fat sources. CSB as a fat source, did not alter the beef pH, shear force, chemical composition, or subcutaneous FA profile compared with the SOB diet. Differences were observed at yellow and red beef color, with low and high CSB diet inclusion; on the contrary, inclusion of SOB in the diet led to an intensely unpleasant aroma in aged and cooked meats. Regarding beef FA profile, CSB with 3% dietary fat produced steaks with a lower proportion of C17:0, having 1.359 and 3.238 g/100 g of intramuscular FA, whereas CSB with 5% dietary fat led to an increase in C18:2n-6, with 0.298 and 0.132 g/100 g of intramuscular FA in steaks from animals fed with CSB and SOB, respectively. CSB produced more intense red beef color, unpleasant aroma, and higher linoleic acid content; however, the color and aroma of the meat produced from cattle fed with CSB in the diet were less intense and were like those observed in cattle fed with SOB; these could therefore be recommended for use as agro-industrial by-products in beef cattle diet.
Subprodutos agroindustriais de caroço de algodão e soja utilizados na dieta de bovinos confinados: efeitos no perfil de ácidos graxos e parâmetros de qualidade da carne bovina
Keywords: Cottonseed; Fat source; Meat quality; Soybean